The Identity of the Main Character in Life of Pi novel by Yann Martel (Psychology of Literature) - Mohamad Sahril (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2015)
The objective of this research was to understand comprehensively the identity of the main character in the novel